2005
DOI: 10.1176/appi.ps.56.7.863
|View full text |Cite
|
Sign up to set email alerts
|

Brief Reports: Outcomes of Patients in a Low-Intensity, Short-Duration Involuntary Outpatient Commitment Program

Abstract: This study examined the outcomes of patients in a low-intensity, short-duration involuntary outpatient commitment program. After release from inpatient commitment, one group (N = 150) entered an involuntary outpatient commitment program that lasted up to six months; a comparison group (N = 140) was released into the community without further involuntary care. After the analysis adjusted for confounding variables, patients who were in the involuntary outpatient commitment program had greater use of follow-up ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
1
18
1
Order By: Relevance
“…In the present work, and in agreement with the medical literature, OPC is applied with greater frequency to persons with schizophrenia (73%). Like other authors, 6 , 21 , 22 , 27 - 29 we found no significant differences between the control and OPC groups in the use of healthcare services: number of emergency visits, number of hospital admissions and average length of hospital stay.…”
Section: Discussionsupporting
confidence: 78%
“…In the present work, and in agreement with the medical literature, OPC is applied with greater frequency to persons with schizophrenia (73%). Like other authors, 6 , 21 , 22 , 27 - 29 we found no significant differences between the control and OPC groups in the use of healthcare services: number of emergency visits, number of hospital admissions and average length of hospital stay.…”
Section: Discussionsupporting
confidence: 78%
“…Involuntary re-admission was reported in both studies [34,35]. One randomised study [35] could not establish a difference in involuntary re-admission between advanced directives and usual care for in-patients about to be discharged from compulsory treatment (p=0.78).…”
Section: Effect On Involuntary Admissionmentioning
confidence: 90%
“…An overview of full text excluded studies in the update (N=4) are listed in Appendix II. Davidson and Campbell [26] 2007 Northern Ireland A) in community Wierdsma, et al [27] 2007 Netherlands A) in community Johnson, et al [28] 2005 England A) in community Henderson, et al [29] 2004 England A) in community Putkonen, et al [17] 2013 Finland B) in hospital Van De Sande, et al [30] 2011 Netherlands B) in hospital Ohlenschlaeger, et al [31] 2007 Denmark B) in hospital Abderhalden, et al [32] 2008 Switzerland B) in hospital Rosenman, et al [33] 2000 Australia B) in hospital Pollack, et al [34] 2005 USA C) at discharge Papageorgiou, et al [35] 2002 England C) at discharge…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The AOT sample was identified by the mental health services board and consisted of all who had been receiving AOT for at least 6 months from 2000 through 2005. We excluded individuals who were receiving AOT for fewer than 6 months because prior research suggested this length of time was needed to achieve reductions in psychiatric hospitalizations (3,9). For the sample of 74 individuals, we examined changes in the number of days of psychiatric hospitalization before, during, and after AOT.…”
Section: Methodsmentioning
confidence: 99%